Waiting for Black Superman: A Look at a Problematic Assumption - Pabon, Amber (Urban education (Beverly Hills, Calif.), 2016)
Black male teachers make up less than 2% of the U.S. public school labor force. A prevalent discourse among educational stakeholders has suggested that Black male teachers are the key to helping students in urban schools develop skills to succeed in school by acting as role models. This assertion presents Black male teachers as a panacea to improving urban schools while ignoring the historical and contemporary contexts that complicate their roles in schools. This study uses life history methods to access the narratives of a group of Black male teachers to shed light on their experiences working in urban classrooms. The purpose of this study is to broaden our understandings about teacher education, teaching, and teacher retention of Black male teachers.